Reverse Takotsubo Cardiomyopathy Following Exploratory Laparotomy. (2nd March 2018) - Akel, Tamer; Barsoum, Emad; Mroue, Jad; Nalluri, Nikhil; Tamburino, Frank; Bogin, Marc
Reverse takotsubo cardiomyopathy is an uncommon cardiomyopathy characterized by reversible regional wall motion abnormalities in the basilar segment of the left ventricle. This happens in the absence of any coronary artery pathology. Although it shares some pathogenic mechanisms with its more common variant, takotsubo cardiomyopathy, differences exist in terms of echocardiographic features, demographics, clinical manifestations, laboratory features, and prognosis. Cases of postoperative reverse takotsubo cardiomyopathy are less described in the literature. Herein, we report a case of reverse takotsubo cardiomyopathy in a 44-year-old woman occurring after exploratory laparotomy.